Screening for hemoglobinopathies in a socially disadvantaged population from a rural district of West Bengal, India - Mandal, Prakas Kumar; Dolai, Tuphan Kanti; Mandal, Soma; Mondal, Tamanash; Maji, Suman Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Detection of traits/carriers plays an important role in preventing the birth of a thalassemic child. West Bengal, one of the eastern states in India is the home to a bulk of socially challenged population including scheduled castes and scheduled tribes among others. The present study aimed to detect the prevalence of different hemoglobinopathies in a socially challenged district of West Bengal. Methods: In this retrospective cross sectional study thalassemia detection camps were organized at the community level over a period of four years. Venous blood samples were subjected to complete hemogram and high performance liquid chromatography (HPLC). In few difficult cases samples were sent to the reference laboratory for molecular characterization. The prevalence of heterozygous, homozygous or compound heterozygous states of different thalassemias and hemoglobinopathies across various respondent groups (e.g. children, premarital, postmarital and antenatal) and existing caste categories (scheduled tribes, scheduled caste and general) were analyzed. Results: We analyzed a total of 114,606 HPLC reports; 18681 (16.30%), 15438 (13.47%) and 80487 (70.23%) cases belonged to scheduled tribes, scheduled castes and general category respectively. Out of 114,606 cases, 11,001 (9.6%) had revealed abnormal hemoglobins; beta thalassaemia trait was the most common (6.63%; n=7602) across all subgroup analysis. Among others, HbE trait, sickle cell trait and HbD trait were detected in 1788 (1.56%), 1362 (1.18%) and 126 (0.11%) cases respectively. Conclusions: Beta thalassaemia trait and HbE trait are the common haemoglobin variants in this rural district of West Bengal. The prevalence of sickle gene revealed in the present study is much less than previous studies in the locality.